Budget Deficits and Economic Growth: A Vector Error Correction Modelling of South Africa - Molefe, Kagiso; Maredza, Andrew (Journal of Economics and Behavioral Studies, 2017)
The primary motivation behind this study was to explore the consequential effects of budget deficit on South Africa`s economic growth. Six variables were used, namely: real GDP, budget deficit, real interest rate, labour, gross fixed capital formation and unemployment. The Vector Error Correction Model (VECM) was used to estimate the long-run equation and also measure the correction from disequilibrium of preceding periods. Using annual time series data spanning the period 1985 to 2015, empirical evidence from the study revealed that budget deficits and economic growth are inversely related. It was therefore concluded that high levels of budget deficit in South Africa have detrimental effects on the growth of the economy. The estimate of the speed of adjustment coefficient found in this study revealed that about 29 per cent of the variation in GDP from its equilibrium level is corrected within one year. The results obtained in this study are favourably similar to those in the literature and are also sustained by previous studies.